Construction method and performance analysis of chaotic frequency-hopping sequences based on Logistic-Sine-Cosine mapping - CAO Chunjie; WANG Yinglin; SUN Yang; TAO Hongfei; YANG Haoning; SHI Jingcheng; DAI Junhao; SUN Jingzhang (Tongxin xuebao)
In order to solve the problems of low dimensional chaotic mapping, limited chaotic behavior, and discontinuous chaotic interval, a new construction method of chaotic frequency-hopping sequence was proposed. First, a new Logistics-Sine-Cosine chaotic map was generated by Cosine transformation method combined with Logistic and Sine mapping. Then, the intermediate multi-bit extraction method was used to quantify the sequence generated by the mapping as a frequency-hopping sequence. Finally, experiments show that the chaotic frequency-hopping sequence can effectively improve the randomness and complexity of the sequence under the premise of maintaining good balance and Hamming correlation, and can strengthen the anti-prediction and anti-interference in the communication process.